Global hotspots for soil nature conservation - Guerra, Carlos A (2022)
Soils are the foundation of all terrestrial ecosystems1. However, unlike for plants and animals, a global assessment of hotspots for soil nature conservation is still lacking2. This hampers our ability to establish nature conservation priorities for the multiple dimensions that support the soil system: from soil biodiversity to ecosystem services. Here, to identify global hotspots for soil nature conservation, we performed a global field survey that includes observations of biodiversity (archaea, bacteria, fungi, protists and invertebrates) and functions (critical for six ecosystem services) in 615 composite samples of topsoil from a standardized survey in all continents. We found that each of the different ecological dimensions of soils-that is, species richness (alpha diversity, measured as amplicon sequence variants), community dissimilarity and ecosystem services-peaked in contrasting regions of the planet, and were associated with different environmental factors. Temperate ecosystems showed the highest species richness, whereas community dissimilarity peaked in the tropics, and colder high-latitudinal ecosystems were identified as hotspots of ecosystem services. These findings highlight the complexities that are involved in simultaneously protecting multiple ecological dimensions of soil. We further show that most of these hotspots are not adequately covered by protected areas (more than 70%), and are vulnerable in the context of several scenarios of global change. Our global estimation of priorities for soil nature conservation highlights the importance of accounting for the multidimensionality of soil biodiversity and ecosystem services to conserve soils for future generations.